Hazard Identification and Risk Assessment with Recommended Alternative Solutions Using the Benefit Cost Analysis Method - Rina Sandora; Fani Sandy Putra; Galih Anindita (UNIPA PRESS, 2021)
Determination of hazard identification and risk assessment on the company can not be separated from the calculation of the cost budget. The aim is to provide recommendations and calculate the profit rate using the Benefit Cost Analysis (BCA) method so that the company will more easily determine the most appropriate and needed alternative in the company. From the incremental analysis calculation, an alternative solution and value obtained from BCA are gas detector H2S B / C ratio 1.14, crane certification B / C ratio 3.66, welding helmet B / C ratio value 5.53, wire rope B / C ratio value of 5.19, O2 detector value of B / C ratio 6.11, small handtruck value of B / C ratio 18.1, fire dry chemical powder B / C ratio value of 22.27, N2 gas detector value of ratio B / C 1.53.